The world’s engagement with Algeria’s revolutionary experience: Selected case studies - Hadjersi, Khadra (The International tax journal, 2026)
Algeria succeeded in becoming a concrete embodiment of the successful struggle against settler colonialism. It is beyond doubt that this pioneering revolutionary experience played a decisive role in galvanising the determination of militants throughout the Third World, owing primarily to the revolutionary principles it championed — above all, the right of peoples to self-determination. Algeria therefore committed itself to supporting just causes across the Third World and called for the liquidation of colonialism in all its forms and vestiges, particularly after independence. Algerian foreign policy thus became a natural extension of these revolutionary principles. Algeria demonstrated its capacity to honour its commitments toward every just cause in the world, and its support for liberation movements was neither incidental nor temporary; it was a principled stance destined to endure, founded on the recognition that liberation movements represent a form of international conflict to which international law must be applied.